2020
DOI: 10.3390/ijerph17218112
|View full text |Cite
|
Sign up to set email alerts
|

Non-Smoker’s Exposure to Second-Hand Smoke in South Africa during 2017

Abstract: Current South African tobacco control law allows for 25% designated smoking areas in some indoor public places. This study investigates non-smokers’ exposure to second-hand smoke (SHS) in workplaces, homes, cafés/restaurants, and shebeens (local bars) using data from the 2017 South African Social Attitude Survey. Factors associated with any level of exposure were explored using multiple-variable-adjusted logistic regression analysis. The sample of 3063 participants (16+ years old), comprised 51.7% females and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…In Farafenni, higher education was also a strong protector of being exposed to second-hand smoke, suggesting that increasing public awareness is a good strategy. Our findings also concur with a study in Mongolia and China where among non-smoking women, those with a higher education were less likely to be exposed to second-hand tobacco smoke compared to those with a lower level of education [ 12 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In Farafenni, higher education was also a strong protector of being exposed to second-hand smoke, suggesting that increasing public awareness is a good strategy. Our findings also concur with a study in Mongolia and China where among non-smoking women, those with a higher education were less likely to be exposed to second-hand tobacco smoke compared to those with a lower level of education [ 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…Preliminary analysis of the 2017 GYTS revealed that 61.8% of students (13–15 years old) were exposed to second-hand smoke in enclosed public places [ 3 ]. In our study, women were much less exposed in both indoor and outdoor public places, a finding that is similar to results from South Africa where females were less likely to be exposed in all locations except their homes [ 12 ]. In India, males were also more likely to be exposed in public places, but females were more likely to be exposed at home [ 13 ].…”
Section: Discussionsupporting
confidence: 89%
“…As a result, the combined use of tobacco and alcohol is associated with poor infant outcomes, including poor growth [ 4 ]. It is also worth noting that second hand smoke (SHS), which usually occurs at home, work, and hospitality venues [ 35 ], affects children and women in their daily lives [ 36 ], and brings about almost the same adverse health outcomes as active smoking [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, non-smokers may be subjected to SHS in public places, the workplace, or in their home. Many countries have issued smoke-free policies to help reduce SHS exposure in public places and workplaces, but not in the home ( 11 ). Because nurses work in hospitals, which are smoke-free environments, they are an appropriate target group to examine the relationship between exposure to SHS in non-workplace environments and health.…”
Section: Introductionmentioning
confidence: 99%